Formulasi Strategik Kepala Sekolah dalam Membangun Budaya Mutu di Sekolah Dasar/Madrasah Ibtidaiyah Tenggarong, Kalimantan Timur - Akhmad, Akhmad; Dwiyono, Yudo; Anggreini, Putri (Abdimas Indonesian Journal, 2025)
Quality culture is a fundamental element in improving the quality of education in basic education units. Principals and vice principals have a strategic role in shaping a culture of quality through systematic planning, organization, implementation, and evaluation. This community service activity aims to increase the understanding of principals and deputy principals of elementary/MI schools in Tenggarong City regarding strategic formulations in building a culture of quality in their respective school environments. The activity will be held in June 2025 at the Kutai Kartanegara Regency Library Building, Tenggarong. The implementation method includes the delivery of materials, workshops, and interactive discussions that actively involve participants. The results of the activity showed an increase in participants' understanding of the concept of quality culture as well as the initial ability to develop strategic plans based on school conditions. This activity is expected to be the first step in strengthening the managerial capacity of school principals to encourage the creation of a sustainable quality culture in elementary schools and madrasah ibtidaiyah.